The Influences of Change Readiness and Self-Efficacy on Teacher Performance during the COVID-19 Pandemic - Mega Alawiyah Maksum; Joko Purwono; Furqon Syarief Hidayatullah (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Covid-19 epidemic has also had an impact on the work environment for teachers who used to teach in schools but now work from home (WFH) at home. To succeed in these shifting situations, teacher preparation must be improved. Personal preparedness (self-efficacy) is strongly linked to change readiness, which is useful for increasing student learning outcomes. This study intends to investigate the relationship between elementary school teachers' readiness for change and their self-efficacy during the Covid-19 pandemic in Cibitung Regency, as well as the readiness for change in self-efficacy in Cibitung Regency during the Covid-19 pandemic. The study gathered data from 135 people using probability sampling and cluster random sampling procedures, and then analyzed it using SmartPLS 3.0 software and Structural Equation Modeling - Partial Least Squares (SEM PLS). The results revealed that changing intentions had a 60.5 percent effect on teacher performance, self-efficacy had a 22.4 percent influence on teacher performance, and changing intentions had a 60.6 percent effect on self-efficacy. Many schools have stopped receiving quota help from the Ministry of Education and Culture, which has hampered online learning and potentially harmed teacher effectiveness. It is expected that stakeholders, particularly school principals, the Education Office, and the Ministry of Education and Culture, will continue to offer data internet in order to improve education in Cibitung Regency's public elementary schools. single space.